2019
DOI: 10.1177/1753944719840192
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of chronic heart failure pharmacotherapy treatment approaches in African Americans

Abstract: Background: Our aim was to review the published literature evaluating treatment approaches for chronic heart failure (HF), notably as it relates to African American patients. Method: We undertook a comprehensive database search (1986–2017) of PubMed, EMBASE, and Ovid/MEDLINE utilizing terms ‘African American’, ‘black’, ‘chronic heart failure’, ‘heart failure’, ‘medication’, ‘chronic therapy’, and ‘clinical trials’. Additional notable studies were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…CHF has become a serious public health problem worldwide, and epidemiological data in recent years has reported that the prevalence of heart failure in China is 0.9%, with 4.5 million patients suffering from heart failure and about 500,000 new cases of heart failure each year [18][19][20]. Various end-stage cardiac diseases can lead to heart failure to varying degrees, including coronary heart disease, hypertension, arrhythmias, heart valve disease, and cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…CHF has become a serious public health problem worldwide, and epidemiological data in recent years has reported that the prevalence of heart failure in China is 0.9%, with 4.5 million patients suffering from heart failure and about 500,000 new cases of heart failure each year [18][19][20]. Various end-stage cardiac diseases can lead to heart failure to varying degrees, including coronary heart disease, hypertension, arrhythmias, heart valve disease, and cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 6 For instance, in the United States (U.S.) and the United Kingdom (UK) black people have a higher HF prevalence rate, less access to advanced healthcare, and poorer HF outcomes compared to white people. 7 , 8 , 9 In addition, HF studies in Afro-Caribbeans show that the risk of HF in that population aged 60-79 years is as much as 3.1 higher than in Caucasians, and that HT is the main cause of HF in the Afro-Caribbean population. 10 , 11 Various authors have suggested that the role social determinants of health, such as environment, lifestyle, access to care as well as comorbidities, play in the outcomes between different ethnicities must be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…There have been improvements in mortality rates, quality of life and reductions in HF exacerbations in some populations. 9 , 17 Primarily, HF care has improved in high Income countries (HIC), with extensive healthcare resources including dietary interventions, exercise and cardiac rehabilitation programs. However, even in HIC, there are healthcare delivery discrepancies resulting in often intransigent health disparities, and progress is lacking in promoting healthy lifestyles and medication adherence.…”
Section: Introductionmentioning
confidence: 99%
“…This insufficient knowledge base regarding medication effect is even more challenging given the higher prevalence of certain comorbid conditions (e.g. chronic kidney disease, diabetes, amyloidosis), and more limited access to care, in African American patients with HFrEF [ 15 ]. As the first study to report the efficacy and safety of ivabradine specifically in self-identified African American patients with HFrEF, the current work represents a valuable addition to the literature and has the potential to inform clinical guidelines [ 2 ].…”
Section: Discussionmentioning
confidence: 99%